Speed Advice for Power Efficient Drawbar Work - Peça, José M. (2012)
Tractor manufacturers already offer engine – transmission control systems in which the operator decides whether low fuel consumption or high output is the priority and let a control system provide engine and transmission management. Less sophisticated tractors, as well as older equipment, still rely on the operator awareness upon what driving parameters most enhance efficiency. The objective of this study is to analyse the effect of driving parameters, namely forward speed and engine speed on the overall power efficiency. The overall power efficiency of a tractor performing drawbar work is the ratio between the output power at the drawbar and the energy equivalent of the fuel consumed per unity of time. Experimental data obtained from tractor field tests in real farm conditions, within the range of 0.2 to 0.4 for the dynamic traction ratio (ratio of the drawbar pull to the total weight of the tractor), show that increments of 10 % to 20 % on the overall power efficiency can be obtained by throttling down from 2200 min-1 to 1750 min-1 (idle speed). The reduction in ground speed and therefore in the work rate, may be overcome by shifting up the transmission ratio.